Influence of 4f hybridization on the structural and electronic properties of CeM2Si2 (M=Ru, Rh, and Pd) - Vildosola, V. (2004)
Fil: Vildosola, V. Comisión Nacional de Energía Atómica; Argentina; Universidad de Buenos Aires; Argentina